From Oxford to Williamsburg: part 1 – the University of Oxford, Faculty of Law and Bodleian Law Library - Bird, R (Cambridge University Press, 2012)
The Bodleian Law Library has only existed as an entity in its own right for less than 50 years. Yet part of the collection dates back to the days before the founding of the Bodleian Library in 1602. The rise and fall in fortunes of the teaching of law at Oxford is closely tied to the establishment of the law library. A lesser known aspect of the history includes the ties between Oxford and the United States, especially its oldest law school, William and Mary Law School. In this paper, Ruth Bird offers a brief history of the University of Oxford and then looks at the history of law teaching, before moving on to the evolution of the Law Library itself, and some links with our cousins across the pond.